2020
DOI: 10.14195/1647-8606_63-2_7
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Mindfulness in Parenting Scale – Infant Version

Abstract: The present study aims to explore the factor structure and psychometric properties of an adapted version of the Portuguese version of the Interpersonal Mindfulness in Parenting Scale for parents of infants aged 0 to 12 months (the IM-P-I). Two studies were conducted. The first study included 560 postpartum mothers and examined the factor structure and internal consistency of the IM-P-I. The second study included 295 postpartum mothers, with the goal of cross-validating the factor structure of the questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Because four items were omitted from the IMP for the IMP-I (Items 4, 7, 8, 28), the CC subscale was comprised of three items rather than the six items used by Moreira and Canavarro (2017), and the SRP subscale was comprised of seven rather than eight items. Reliability estimates for all dimensions were sound and equivalent to those reported in other studies (Caiado et al, 2021;Fernandes et al, 2021): LFA (α = 0.82; ω = 0.82); EAC (α = 0.62; ω = 0.63); SRP (α = 0.68; ω = 0.62); NJAPF (α = 0.75; ω = 0.76); and CC (α = 0.75; ω = 0.76). Prior research has found that the total mindful parenting score and dimensions (subscales) have sound discriminant validity with measures of parent psychopathology (Caiado et al, 2021;Fernandes et al, 2021).…”
Section: Mindful Parentingsupporting
confidence: 79%
See 2 more Smart Citations
“…Because four items were omitted from the IMP for the IMP-I (Items 4, 7, 8, 28), the CC subscale was comprised of three items rather than the six items used by Moreira and Canavarro (2017), and the SRP subscale was comprised of seven rather than eight items. Reliability estimates for all dimensions were sound and equivalent to those reported in other studies (Caiado et al, 2021;Fernandes et al, 2021): LFA (α = 0.82; ω = 0.82); EAC (α = 0.62; ω = 0.63); SRP (α = 0.68; ω = 0.62); NJAPF (α = 0.75; ω = 0.76); and CC (α = 0.75; ω = 0.76). Prior research has found that the total mindful parenting score and dimensions (subscales) have sound discriminant validity with measures of parent psychopathology (Caiado et al, 2021;Fernandes et al, 2021).…”
Section: Mindful Parentingsupporting
confidence: 79%
“…Reliability estimates for all dimensions were sound and equivalent to those reported in other studies (Caiado et al, 2021;Fernandes et al, 2021): LFA (α = 0.82; ω = 0.82); EAC (α = 0.62; ω = 0.63); SRP (α = 0.68; ω = 0.62); NJAPF (α = 0.75; ω = 0.76); and CC (α = 0.75; ω = 0.76). Prior research has found that the total mindful parenting score and dimensions (subscales) have sound discriminant validity with measures of parent psychopathology (Caiado et al, 2021;Fernandes et al, 2021).…”
Section: Mindful Parentingsupporting
confidence: 79%
See 1 more Smart Citation
“…On the one hand, one might assume mindful parenting to relate to mothers’ own prosocial behaviours through common themes such as kindness, understanding and empathy in these constructs and thus to be related to children's prosociality through both environmental and genetic provision (Knafo & Plomin, 2006). On the other hand, mindful parenting may be more pertinent to children's problem behaviours than prosocial behaviours through emotion regulation skills pertinent to mindful parenting (Caiado et al., 2020) as well as to a lack of parental reactivity and harshness (Crandall et al., 2015). Alternatively, given the potential bidirectional nature of the relationships between mindful parenting and child behaviours (e.g., Kim & Gonzales, 2021), we might also argue more problem behaviours are detrimental to mindful parenting, while more prosocial behaviours do not promote mindful parenting as they are more “typical” (Wang et al., 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Related dimensions included: Parental warmth, sensitivity, acceptance, (postnatal) attachment, involvement, cohesiveness, (emotional) support, (un)labeled praise, and mindful parenting. • Self-report measures: Alabama Parenting Questionnaire (Frick, 1991); Parenting Questionnaire (McCabe et al, 1999); Parental Acceptance-Rejection Questionnaire (Rohner et al, 2005); Parenting Relationship Questionnaire (Kamphaus & Reynolds, 2006); Maternal Postnatal Attachment Scale (Condon & Corkindale, 1998); Interpersonal Mindfulness in Parenting Scale (-Infant version;Caiado et al, 2020;Duncan, 2007;Moreira & Canavarro, 2017) • Observational coding systems: Dyadic Parent-Child Interaction Coding System (Eyberg et al, 2010); The Family Interaction Drawing Task (Cox et al, 1998;Lindahl & Malik, 2001;McHale & Fivaz-Depeursinge, 1999); Emotional Availability Scales (Biringen et al, 2014) Aspects of parenting with negative valence Similarly, several aspects of parenting with negative valence were assessed using self-report measures and observational coding. Related dimensions included: Dysfunctional discipline practices (laxness, over-reactivity, and hostility), corporal punishment, negative talk, rejection, demandingness, and relational frustration.…”
Section: Aspects Of Parenting With Positive Valencementioning
confidence: 99%